Expression of Estrogen Receptor β in Hypothalamic Stem Cells - Zhen He; Li Cui; Sherry A. Ferguson; Merle G. Paule (Journal of Evolving Stem Cell Research, 2017)
Neural stem cell activity at least partially accounts for the postweaning development of the sexually dimorphic nucleus of the preoptic area (SDN-POA) and estrogen selectively mobilizes neural stem cells in the 3rd ventricle stem cell niche (3VSCN). Here, we examined the expression of estrogen receptor β (ERβ) in the SDN-POA and the 3VSCN. A subset of cells within the SDN-POA–delineated with or without calbindin D28K (CB28)-immunoreactivity (ir)–exhibited ERβ-ir. The ependymal cells that expressed nestin within the 3VSCN also expressed ERβ. Interestingly, a few proliferating (Ki67 positive) cells within the 3VSCN and the hypothalamic parenchyma, including the SDN-POA, displayed ERβ-ir. In parallel, a subset of cells in the subventricular zone was double-labeled with nestin and ERβ or Ki67 and ERβ while the subgranular zone exhibited few such double-labeled cells. ERβ is expressed in hypothalamic stem cells that may regulate cell regenerative cycles.
Keywords: Estrogen receptor beta